Childhood cancer: feelings expressed by children in chemotherapy during therapeutic toy sessions - Souza, Luís Paulo Souza e; Silva, Raiane Katielle Pereira; Amaral, Renata Guimarães; Souza, Ana Augusta Maciel de; Mota, Écila Campos; Silva, Carla Silvana de Oliveira e (Rev Rene, 2012)
This study aimed at understanding the feelings experienced by the child with cancer manifested during Therapeutic Toy sessions. This qualitative research was performed with five children aged between three and twelve years, of both sexes. Data collection was carried out through a participatory and systematic observation, coupled with interviews intermediated by Therapeutic Toy Sessions. The data was worked using discourse analysis. The child with cancer was shown as a being full of feelings. The fear of death, pain, sadness on the limitations imposed by the disease, the withdrawal and rebellion with the procedures, the anguish in the face of uncertainties were negative feelings expressed by the children in the dramatizations. However, the development of treatment, the manifestation of a good prognosis and outcome of cure were emerging feelings of hope and happiness before the treatment, optimism in return to usual activities and overcoming amidst the difficulties experienced.